The representation of geometric concepts in Grade 6 Mathematics textbooks: a socio-cultural analysis - Barnard, Marelize (School of Education, 2016)
In this study Vygotsky's theory of concept formation is used to gain insight into the representation of geometric concepts in grade six mathematics textbooks. According to Vygotsky, higher order mental functioning is developed when scientific and everyday concepts are dialecfoally linked. The textbook as a mediating artefact has an important role to play in the process of concept formation. To determine if the geometry of space and shape is presented as scientific concepts in the text, content analysis of three randomly sampled grade six mathematics textbooks were conducted. The analysis included an investigation of what misconceptions exist in the text and what level of cognitive demand is required by the textbook tasks and activities. The initial structure for the research was derived from Valverde et al. (2002)'s methodology after which frameworks for the content analysis were developed for the distinction between everyday and scientific concepts, the identification of misconceptions and the classification of levels of cognitive demand. The results not only showed a low prevalence of scientific concepts, but also high incidences of misconceptions put forward in the textbooks. There were few textbook tasks and activities that required problem-solving, thereby limiting the learner to lower order thinking.